The Implications of Covid-19 on Increased Social Distancing for At-Risk Youth in Israel’s Arab Community - Badir, Rodayna Kamal; Abu Saleh, Anan; Nasrallah, Omar AbdAlrahim (Journal of Humanities & Social Sciences, 2023)
The study examined the repercussions of Covid-19 on the intensification of increased social distancing of at-risk youth in Israel’s Arab community. The study was conducted by utilizing quantitative methodology which examined a total sample of (160) young people aged 18-25 years; (80) of whom were at risk and (80) considered not at risk. In the hypothesis, the tendency towards social distancing was studied within the permanence of several variables, which included; the level of education of the participants, the spectrum of emotional status and experience (namely, fear, guilt, love, tolerance, empathy and compassion), and finally the set of behaviors exhibited to prevent infection with Covid-19. Conclusively, the study notably drew a quantitative comparative examination of both categories in the samples. The results of the examination were premised on two indicators of social distancing: the tendency to be close to those infected, and the tendency towards social distancing. The results seemingly draw a positive relationship between these indicators and feelings of guilt and fear of social distancing, with fear negatively associated with the tendency to approach in close proximity. The study found that the participants who were infected with Covid-19 had maintained the lowest inclination for social distancing while exhibiting a lower level of fear, while highlighting a positive relationship between the level of education and the index of propensity towards proximity in the social distancing variable. Furthermore, it found that the level of education was higher among young people who were not at risk. The study’s contribution to expanding the field of research on the issue of Covid-19 and its repercussions is reflected in the context of stigma and social distancing, and in focusing on a special and unique group of at-risk youth in Arab society.